2002
DOI: 10.1046/j.1365-2141.2002.03479.x
|View full text |Cite
|
Sign up to set email alerts
|

Roles for both cyclic GMP and cyclic AMP in the inhibition of collagen‐induced platelet aggregation by nitroprusside*

Abstract: Summary. In studies on human platelets, nitroprusside (NP) alone at 1-10 lmol/l increased platelet cyclic AMP (cAMP) by 40-70%, whereas increases in cyclic GMP (cGMP) were much larger in percentage though not in concentration terms. Collagen enhanced these increases in cAMP up to fourfold, without affecting cGMP. This effect was partly prevented by indomethacin or aspirin, indicating that platelet cyclo-oxygenase products acted synergistically with NP to increase cAMP. ADP released from the platelets by collag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
37
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 45 publications
7
37
0
Order By: Relevance
“…6A, B), which is in accord with reports that the inhibition of agonists-induced platelet aggregation is dependent on inhibition of COX-1 rather than TXAS (Lewis and Watts, 1982;Jang et al, 2002). Because these results suggest that inhibition of TXA 2 by RBLw is responsible for the suppression of microsomal specific COX-1, it is shown that RBLw may be used as a COX-1 inhibitor.…”
Section: Discussionsupporting
confidence: 80%
“…6A, B), which is in accord with reports that the inhibition of agonists-induced platelet aggregation is dependent on inhibition of COX-1 rather than TXAS (Lewis and Watts, 1982;Jang et al, 2002). Because these results suggest that inhibition of TXA 2 by RBLw is responsible for the suppression of microsomal specific COX-1, it is shown that RBLw may be used as a COX-1 inhibitor.…”
Section: Discussionsupporting
confidence: 80%
“…Epinephrine-mediated α2A-adrenoceptor-coupled Gz signaling alone is known to be incapable of inducing full platelet aggregation, and activation of P2Y12 receptor-coupled Gi signaling, which leads to inhibition of adenylyl cyclase, is required (22)(23)(24). An elevated plasma level of NO has been observed in CA-HY compared to CA-GR (10), and NO is known to raise cAMP levels in platelets (25). However, it is consistent with previous reports that inhibition of cAMP accumulation by epinephrine was not significantly different between epinephrine hypo-responders and epinephrine normal responders (9, 10, 26, 27).…”
Section: Discussionmentioning
confidence: 99%
“…Although it was believed that cGMP inhibits platelet activation by activating PKG, we have shown that PKG in fact plays an important stimulatory role in platelet activation (28,30,36), as PKG knock-out mouse platelets and PKG inhibitor-treated human platelets showed significantly reduced platelet aggregation in response to low dose agonists including soluble agonists thrombin, thromboxane A2, and adhesive proteins VWF and collagen. On the other hand, the inhibitory effects of NO donors and cGMP analogs on human platelets were reversed by inhibitors of cAMPdependent protein kinase (37) and adenylyl cyclase (38), indicating that these effects require elevation of cAMP, possibly induced by inhibition of cGMP-regulated phosphodiesterase 3 (31). Thus, NO exerts biphasic FIGURE 5.…”
Section: Discussionmentioning
confidence: 99%